Biodegradation of polycyclic aromatic hydrocarbons in contaminated soils using a tripartite association of ectomycorrhizal fungi, pine plant and their rhizosphere bacteria - Thantsha, Mapitsi Silvester (2026)
Thesis (PhD (Microbiology))--University of Pretoria, 2018.